Nicola Scaldaferri e Steven Feld (a cura di), I suoni dell'albero – Il Maggio di S. Giuliano ad Accettura (Altre Modernità, 2017)
Nicola Scaldaferri e Steven Feld (a cura di), I suoni dell'albero – Il Maggio di S. Giuliano ad Accettura